Metformin Reduces Aging-Related Leaky Gut and Improves Cognitive Function by Beneficially Modulating Gut Microbiome/Goblet Cell/Mucin Axis. (4th March 2020) - Ahmadi, Shokouh; Razazan, Atefeh; Nagpal, Ravinder; Jain, Shalini; Wang, Bo; Mishra, Sidharth P; Wang, Shaohua; Justice, Jamie; Ding, Jingzhong; McClain, Donald A; Kritchevsky, Stephen B; Kitzman, Dalane; et al.
Abstract: Aging-related illnesses are increasing and effective strategies to prevent and/or treat them are lacking. This is because of a poor understanding of therapeutic targets. Low-grade inflammation is often higher in older adults and remains a key risk factor of aging-related morbidities and mortalities. Emerging evidence indicates that abnormal (dysbiotic) gut microbiome and dysfunctional gut permeability (leaky gut) are linked with increased inflammation in older adults. However, currently available drugs do not treat aging-related microbiome dysbiosis and leaky gut, and little is known about the cellular and molecular processes that can be targeted to reduce leaky gut in older adults. Here, we demonstrated that metformin, a safe Food and Drug Administration-approved antidiabetic drug, decreased leaky gut and inflammation in high-fat diet-fed older obese mice, by beneficially modulating the gut microbiota. In addition, metformin increased goblet cell mass and mucin production in the obese older gut, thereby decreasing leaky gut and inflammation. Mechanistically, metformin increased the goblet cell differentiation markers by suppressing Wnt signaling. Our results suggest that metformin can be used as a regimen to prevent and treat aging-related leaky gut and inflammation, especially in obese individuals and people with western-style high-fat dietary lifestyle, by beneficially modulating gut microbiome/goblet cell/mucin biology.